Adhesive Failure of Lava Ultimate and Lithium Disilicate Crowns Bonded to Zirconia Abutments: A Prospective Within-Patient Comparison - Schepke, Ulf; Lohbauer, Ulrich; Meijer, Henny J.; Cune, Marco S. (International Journal of Prosthodontics, 2018)
PURPOSE: To demonstrate the influence of restorative material on the success of clinical bonding to zirconia. MATERIALS AND METHODS: A total of 50 participants with a single implant received screw-retained restorations; ie, Lava Ultimate (LU) crowns extraorally bonded to zirconia abutments. After 1 year, lithium disilicate (LDS) was used as an alternative restorative material. These restorations were also followed for 1 year. RESULTS: Forty LU restorations (80%) debonded within 1 year of clinical service, whereas no bonding failures occurred with LDS restorations. CONCLUSION: The choice of restorative material for single crowns luted to zirconia implant abutments strongly influences the incidence of bonding failures.
EVALuna2:34641